Kinetics and Mechanism of Mn(II) Catalyzed Periodate Oxidation of p-anisidine: Effect of pH - Rajneesh Dutt Kaushik; Jaspal Singh; M. Manila; Manmeet Kaur; Prabha Singh (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2014)
The stoichiometry for the initial part of the reaction, Mn(II) catalysed periodate oxidation of p-anisidine (PMA), has been found to be 1 mol of PMA consuming 2 mol of periodate ion. The kinetic-mechanistic study of reaction in acetone-water medium was made spectrophotometrically by noting the increase in the absorbance of reaction intermediate. Reaction is first order in reactants and catalyst each. A decrease in dielectric constant of the medium results in decrease in the rate of reaction suggesting an ion-dipole type interaction. Free radical scavengers do not affect the reaction rate. A special type of rate-pH profile shows a maximum at pH = 7.0. This pH effect also suggests the involvement of at least three differently reactive reactant species in the reaction and this fact has been considered by us while deriv-ing the rate law. Under pseudo first order conditions [IO4-] >> [PMA] and in agreement with the derived rate law, the 1/kcat versus [H+] plot passes through the minimum and the results can be fitted to the equation: 1/kcat = (K2 / k K3 K4 [H+]) + (Kw + Kb K2) / k K3 K4 Kw + Kb [H+] / k K3 K4 Kw, where kK3K4 is the empirical composite rate constant, Kw is ionic product of water, K2 is acid dissociation constant of H4IO6- and Kb is base dissociation constant of PMA. The experimental value of [H+]min is in good agreement with the value calculated by using the derived rate law equation and is character-istic of the substrate involved relating to the base dissociation constant of PMA. The value of thermo-dynamic parameters have been evaluated. © 2014 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0)